THE I-CON MODEL IN CONSTRUCTING MATHEMATICAL PROOF - Mujib, Abdul; Firmansyah, Firmansyah; Siagian, Siti Shara; Mathelinea, Devi (Universitas Labuhanbatu, 2025)
Purpose-This research aims to analyze the role of the I-CON model in constructing mathematical proofs.Methodology-The research used is qualitative with a grounded theory approach. Respondents were selected using a theoretical sampling approach, based explicitly on concepts that have been shown to relate to the theory being developed. Analysis data is obtained based on student test results, which are given to respondents, compiled into a new concept or theme, and then the desired subcategory.Findings- The theory derived from this research is that, through the I-CON model, students can construct robust, precise, and valid mathematical proofs. The implementation of the I-CON model in the ability to construct mathematical proofs is (1) students can link facts with properties to interpret existing problems, (2) students can sequence valid proof steps, (3) students can use premises, definitions, and theorems related to statements to build a proof, (4) students can use appropriate arguments in the proof process, (5) Students have a systematic flow of thinking so that the proof steps are consistent, and (6) Students can interpret symbols mathematical and use precise mathematical communication language, which is obtained through learning the ICON model. Through learning the I-CON model, students can have the ability to understand various concepts, theorems, and definitions. They can make conjectures from statements given by interpreting them in detail. Implementing the Interpretation-Construction Design (I-CON) model in constructing mathematical proof produces six categories: Initial steps of proof, Flow of Proof, Related concepts, Arguments, Interpretation, and Language of Proof.Significance-The results emphasize the importance of students constructing interpretations of real-world problem situations, discussion activities in building interpretations, reflecting, analyzing, and concluding interpretations that students construct as the primary focus of learning activities